High selectivity of CO2 conversion to formate by porous copper hollow fiber: Microstructure and pressure effects. (1st January 2021) - Liu, Defei; Hu, Yan; Shoko, Elvis; Yu, Hongbo; Isimjan, Tayirjan Taylor; Yang, Xiulin
Highlights: Copper hollow fiber with interconnected pore structure was fabricated via a controllable method. A high selectivity for CO2 reduction to formate with a maximum FE of 77.1% was achieved at −34.7 mA cm −2 . The high pressure induced unique crystal facets attributes to the superior electrocatalytic activity and selectivity. Abstract: Electrochemical reduction of CO2 by Cu hollow fibers to CO with high selectivity has previously been reported but selective conversion of CO2 to formic acid at high current densities, although highly desirable, is still challenging. Herein, a Cu hollow fiber with an interconnected pore structure is fabricated via a facile method and used as a stand-alone cathode for highly efficient electrochemical reduction of CO2 to formate. We obtain a high selectivity for CO2 reduction to formate with a maximum FE of 77.1% at a high current density of 34.7 mA cm −2, one of the highest FE on Cu-based materials. Our results suggest that delivering the CO2 gas into the inner space of the hollow fiber leads to a higher CO2 partial pressure in the pores due to the pressure drop across the wall of the Cu hollow fiber. As both the CO2 and H + ions (from the electrolyte) compete for adsorption on the Cu hollow fiber active sites, the higher CO2 partial pressure makes CO2 adsorption more favorable, thereby reducing the concentration of the H + on the active sites. This effectively suppresses the major competing reaction, hydrogen evolution reaction (HER), from 46.9% Faradaic efficiency (FE) to 15.0%. Furthermore, our studies reveals the impotency of the co-existence of Cu(100) and Cu(110) active site facets towards excellent selectivity of formate formation under high CO2 partial pressure. Additionally, the designed catalyst also exhibits out-standing long-term stability at high current density, demonstrating potential for large-scale practical applications. Graphical abstract: Image, graphical abstract